PENGEMBANGAN BAHAN AJAR AKUNTANSI UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN DI KELAS - Henny Zurika Lubis; Nina Ismaya (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Sumatera Utara)
This study aims to develop accounting teaching materials and to see the feasibility of teaching materials in improving the quality of classroom learning on the subject matter of the accounting cycle of service companies. This research is a development research adapted from the ADDIE model. There are 5 stages, namely: 1. Analysis (Analysis), 2. Design (Design), 3. Development (Development), 4. Implementation (Implementation), 5. Evaluation (Evaluation). Validation was carried out by material experts, media experts and assessments from class X accounting students of Ar-Rahman Medan Private Vocational School. Based on the assessment of material 1 on the feasibility of teaching materials for accounting books, the average score is 3.87 with the